Pendampingan Program Bimbingan dan Konseling pada Layanan Responsif di MA Raudlatul Ulum - Subahri, Bambang; Mala, Hayatul; Sugianto, Didik; Sa`diyah, Halimatus; Nur, Shodri MHD (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Guidance and counseling (GC or BK in Bahasa Indonesia) services play a strategic role in assisting students in dealing with personal, social, academic, and career-related problems. However, at MA Raudlatul Ulum Sumberanyar, GC services have not been implemented systematically and tend to be replaced by punitive approaches for students who violate school rules. This condition indicates the need to strengthen responsive services through structured mentoring so that the school can establish a GC program foundation that is well-organized and aligned with students’ developmental needs. This mentoring-based study employed a descriptive qualitative method using observation, interviews, direct mentoring, and documentation techniques. The mentoring focused on three forms of responsive services: individual counseling, group counseling, and classical guidance accompanied by social skills training based on collaborative activities. The mentoring activities were conducted to identify students’ main problems and to provide initial interventions relevant to the school context. The results of the mentoring revealed three key findings: (1) low student learning motivation, (2) weak discipline and compliance with school regulations, and (3) the absence of a competent guidance and counseling teacher capable of professionally addressing students’ developmental needs. The mentoring process had a positive impact by increasing students’ understanding of GC services, generating alternative solutions to issues of motivation and discipline, and producing recommendations for the provision of more effective GC services. In conclusion, mentoring the GC program within responsive services at MA Raudlatul Ulum has provided an important foundation for the development of more structured counseling services. The school needs to take follow-up steps by strengthening GC policies and preparing qualified counselors so that responsive services can be implemented sustainably.